Phenolic content and antioxidant activities in red unpolished Thai rice prevents oxidative stress in rats - Rattanachitthawat S. (2014)
Radicals cause cellular damage and eventually progress to chronic diseases. Phenolic compounds play a crucial role in radicals scavenging. In this study, we investigated total anti-oxidant activities, total phenolic content and profiles in color strains of unpolished Thai rice. The level of malondialdehyde was also assayed in rats that consumed unpolished Thai rice. Red color strain had the highest antioxidant activities in all tests. It was also showed the highest phenolic content. Interestingly, total phenolic content was strongly correlated with all anti-oxidant in the methods used: 1,1-diphenyl-2-picrylhydrazyl (r = 0.958, p < 0.01), 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (r = 0.966, p < 0.01) and ferric reducing antioxidant power (r = 0.992, p < 0.01). Malondialdehyde level in high and low dose treated groups were significantly lower than that in the control group of rats that consumed unpolished Thai rice. Red color of unpolished Thai rice, source of phenolic compounds, may play a crucial role in oxidative stress prevention. © 2010 Academic Journals.